Space : the longest goodbye [videorecording (DVD)] - Mizrahy, Ido; Holland, Al; Barron, Kayla; Maurer, Matthias; Coleman, Cady, 1960-; Bocar, Ramachandra (Kino Lorber, Inc., 2024)
In the next decade, NASA will send astronauts to Mars for the first time. Separated from Earth, and unable to communicate with the ground in real-time, crew members will experience extreme isolation that could gravely affect their three-year journey. This Sundance-premiering documentary follows a savvy NASA psychologist tasked with protecting daring space explorers.